IMPROVING STUDENTS’ WRITING ABILITY BY USING LIST, INQUIRE, NOTE CASE STUDY AT AKADEMI ANALIS KESEHATAN MUHAMADIYAH - Fitri Arniati (Jurnal Medika, 2016)
This research aimed at findings out whether or not the students were able to improve their writing strategy and whether the students able to use List, Inquire and Note Strategy in writing or not. This research used a pre – experimental method with one group pre – test and post – test design. The population was the second grade students of Analkes Muhammdiyah Makassar. The sample were 24 students by using purposive sampling by taking one class . The data was analyzed into precentage, mean score analysis and value of t – test. The result of the data analysis showed that the students’ writing achievement, in pre – test was X1 = 54,6 and post – test X2 = 71,1. The result of the t – test value was (24,19) is greater than the t – table value was (2,601) this indicates that the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted. There is significant difference of the students’ writing achievement before and after presenting materials by using LINK strategy. Based on the findings and discussions of the research the writer concludes that using List, Inquire, Note, Strategy can improve the ability of the students of Analkes Muhammadiyah in writing.